2003
DOI: 10.1289/ehp.5957
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, air pollution, and hospitalization for cardiovascular diseases among elderly people in Denver.

Abstract: Daily measures of maximum temperature, particulate matter less than or equal to 10 micro m in aerodynamic diameter (PM10), and gaseous pollution (ozone, nitrogen dioxide, sulfur dioxide, and carbon monoxide) were collected in Denver, Colorado, in July and August between 1993 and 1997. We then compared these exposures with concurrent data on the number of daily hospital admissions for cardiovascular diseases in men and women > 65 years of age. Generalized linear models, assuming a Poisson error structure for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
184
4
10

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 303 publications
(211 citation statements)
references
References 32 publications
13
184
4
10
Order By: Relevance
“…Qian et al (2008) found a synergistic effect of PM 10 and high temperatures on daily cardio-respiratory (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007a;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006) ▪ The elderly and individuals with pre-existing cardio-respiratory disease may be more vulnerable to these effects Altered exposure and risk ▪ Some populations may experience increases or decreases in POP exposures and health risks depending on the region and diet of exposed individuals (Bard, 1999;Gordon, 1997;McKone et al, 1996;Watkinson et al, 2003) ▪ Pesticides may impair mechanisms of temperature regulation especially during times of thermal stress Increased susceptibility to pathogens ▪ Toxicants can suppress immune function, and climate-induced shifts in disease vector range will result in novel pathogen exposure (Abadin et al, 2007;Haines et al, 2006;Lipp et al, 2002;Nagayama et al, 2007;Patz et al, 2005;Rogers and Randolph, 2000;Smialowicz et al, 2001) ▪ Immune system impairment linked to toxicants may increase human vulnerability to climate shifts in pathogens ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible exposures may sensitize individuals to allergic disease ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible mortality in Wuhan, China. The PM 10 effects were strongest on extremely high temperature days (daily average temperature 33.1°C) and weakest during normal temperature days (daily average temperature 18°C).…”
Section: Air Pollutants and Cardio-respiratory Diseasementioning
confidence: 99%
See 4 more Smart Citations
“…Qian et al (2008) found a synergistic effect of PM 10 and high temperatures on daily cardio-respiratory (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007a;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006) ▪ The elderly and individuals with pre-existing cardio-respiratory disease may be more vulnerable to these effects Altered exposure and risk ▪ Some populations may experience increases or decreases in POP exposures and health risks depending on the region and diet of exposed individuals (Bard, 1999;Gordon, 1997;McKone et al, 1996;Watkinson et al, 2003) ▪ Pesticides may impair mechanisms of temperature regulation especially during times of thermal stress Increased susceptibility to pathogens ▪ Toxicants can suppress immune function, and climate-induced shifts in disease vector range will result in novel pathogen exposure (Abadin et al, 2007;Haines et al, 2006;Lipp et al, 2002;Nagayama et al, 2007;Patz et al, 2005;Rogers and Randolph, 2000;Smialowicz et al, 2001) ▪ Immune system impairment linked to toxicants may increase human vulnerability to climate shifts in pathogens ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible exposures may sensitize individuals to allergic disease ▪ Low-income populations, infants, children, and the chronically ill may be more susceptible mortality in Wuhan, China. The PM 10 effects were strongest on extremely high temperature days (daily average temperature 33.1°C) and weakest during normal temperature days (daily average temperature 18°C).…”
Section: Air Pollutants and Cardio-respiratory Diseasementioning
confidence: 99%
“…However, a number of studies suggest that the toxicity of ozone and PM will be exacerbated with global warming, and some of these data support that older adults will be especially vulnerable (Bell et al, 2007;Confalonieri et al, 2007;Dominici et al, 2006;Fiala et al, 2003;IPCC, 2007c;Katsouyanni et al, 1993;Knowlton et al, 2004;Koken et al, 2003;Mauzerall et al, 2005;Ordonez et al, 2005;Rainham and Smoyer-Tomic, 2003;Ren and Tong, 2006). Other potential interactions between climate change and toxicant exposure include increased susceptibility to pathogens (Abadin et al, 2007;Nagayama et al, 2007;Smialowicz et al, 2001) and aeroallergens (D'Amato et al, 2002;Diaz-Sanchez et al, 2003;Epstein, 2005;Janssen et al, 2003).…”
Section: Effects Of Climate Change On Contaminant-linked Human Healthmentioning
confidence: 99%
See 3 more Smart Citations